Art therapy masks reflect emotional changes in military personnel with PTSS - V. Estrada Gonzalez; V. Meletaki; M. Walker; J. Payano Sosa; A. Stamper; R. Srikanchana; J. L. King; K. Scott; E. R. Cardillo; C. Sours Rhodes; A. P. Christensen; K. M. Darda; et al. (Scientific Reports, 2024)
Abstract Among disabling post-traumatic stress symptoms (PTSS) are irritability, aggressive behavior, distressing memories and general impaired cognition and negative mood. Art therapy interventions, including mask-making, can potentially alleviate these symptoms. We tested the hypothesis that art conveys emotions and predicted that blinded viewers would be able to perceive changes in theoretically derived emotional profiles expressed in art made by military personnel with PTSS from the onset to the end of therapy. Five service members and veterans exhibiting PTSS were enrolled in an 8-session art therapy protocol, during which they artistically transformed papier-mâché masks at the beginning and end of the protocol. We found that blinded viewers without knowledge of the masks’ creation stage (onset or end of therapy) read initial masks as conveying more negative emotions (e.g., angry, upset, and challenged) and later masks as conveying more positive emotions (calm and pleasure). Based on the assessments from the blinded evaluators, we infer the emotional transition experienced by the participants was expressed in the masks. In an exploratory arm of the study, we also found that viewers were better able to empathize with the negative emotions experienced by participants with PTSS when asked to explicitly take their perspective.